The Basics of Penicillin Allergy: What A Clinician Should Know - Louis Lteif; Lea S. Eiland (MDPI AG, 2019)
Antimicrobials in the penicillin class are first line treatments for several infectious diseases in the pediatric and adult population today. In the United States, patients commonly report having a penicillin allergy, with penicillin being the most frequent beta-lactam allergy. However, very few patients experience a clinically significant immune-mediated allergic reaction to penicillin. If a true penicillin allergy exists, cross-reactivity to other beta-lactam antimicrobials may occur. Mislabeling patients with penicillin allergy can lead to a higher utilization of second line antimicrobial agents, potentially increasing costs and resistance due to a larger spectrum of activity. Pharmacists play an essential role in inquiring about patient specific reactions to presumed medication allergies and developing a further assessment plan, if needed, to determine if the medication allergy is real.